Dreams: Such Stuff as Literature is Made On A Study of the Idealized Woman in Charles Dickens: Little Dorrit and Great Expectations - Cunnington, Rosamond (My University, 1978)
The worship of the angelic guardian of the hearth is endemic to Victorian novel writing, but she appears no where so frequently as in the work of Charles Dickens. The idealized woman appears in some form in everyone of his major novels. The first portion of this study attempts to look at idealization as a form of psychic process. It tries to discover what causes it and why it takes the form it does. A brief biographical sketch of Dickens early development seeks to apply what we have discovered of Freudian theory to this author's experience to see if some light can be thrown on the haunting reappearance of the ideal woman in his work.
In Freud's The Interpretation of Dreams he interprets his own now famous dream of Irma's injection. His method is to take each line of the dream and analyze it separately. Such a method would be hopelessly cumbersome in the study of a whole novel, and so it has been our purpose in chapters two and three to take important passages descriptive of the heroine and analyze them line by line. We have shown in this way that idealization always calls forth a counterpart to it in the form of a wholly bad character, sister to the idealized good one. We have been able to show that idealization is a psychic defence which makes ambivalence toward the image of woman rather than the exaltation of her which it appears at first glance.
Keywords: English; English Language and Literature; English Language and Literature